The Influence of Financial Technology Dimensions on Financial Inclusion in the Digital Era (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Financial inclusion remains a persistent challenge for Micro, Small, and Medium Enterprises (MSMEs), particularly in accessing formal financial services equitably and sustainably. This study aims to analyze the influence of financial technology (fintech) on financial inclusion among MSMEs in Surabaya City, focusing on how various fintech dimensions contribute to expanding access to financial systems. Key dimensions examined include Crowdfunding and Peer-to-Peer (P2P) Lending, Market Aggregators, Risk and Investment Management, and the Cashless Society. Adopting a quantitative research design, data were collected through a structured survey involving 100 MSME actors selected via purposive sampling. The analytical method employed was multiple linear regression, facilitated by SPSS software. The results demonstrate that all fintech dimensions, both individually and collectively, exert a significant influence on financial inclusion. Among these, the Cashless Society dimension shows the strongest impact, highlighting the critical role of digital payment systems in facilitating MSMEs’ integration into formal financial networks. The findings suggest that fintech adoption can serve as a strategic enabler for MSMEs, particularly those underserved by conventional banking institutions. By leveraging digital platforms and innovative financial solutions, MSMEs can overcome traditional barriers to financial access, thereby enhancing their operational capacity and long-term sustainability. This study contributes to the growing body of literature on digital financial inclusion by offering empirical evidence from a localized context and identifying key fintech drivers that support inclusive economic participation. In conclusion, the integrated application of financial technology presents a viable pathway to strengthen financial inclusion for MSMEs. It also supports broader goals of inclusive and sustainable digital economic growth at the local level. Policymakers, financial institutions, and technology providers are encouraged to collaborate in scaling fintech solutions tailored to the needs of MSMEs, ensuring equitable access and long-term economic resilience.